Edukasi Identifikasi Biaya Kualitas Melalui Pengelolaan Limbah Salon Untuk Efisiensi Operasional - Mega Norsita; Mesha Andina Siregar; Khairunnisa Diniy; Atiqa Cindy Maulida; Nabila Putri Zhafiera (CV. Multi Kreasi Media, 2026)
Waste management in beauty salons is generally focused on maintaining cleanliness and has not been integrated with quality cost identification to support managerial decision-making. As a result, the potential economic benefits derived from waste management activities are often not optimally recognized. This community service program aimed to improve employees’ understanding of quality cost identification through salon waste management to enhance operational efficiency. The partner was Lembuswana Hair Avenue (a pseudonym), a beauty salon located in Samarinda, East Kalimantan, Indonesia. The program was implemented through field observation, interactive education on the concept of cost of quality, group discussions, and the identification of waste management activities based on four quality cost components: prevention costs, appraisal costs, internal failure costs, and external failure costs. The results indicate that participants were able to classify waste management activities into the appropriate quality cost categories and recognize that used plastic bottles and hair waste possess economic value when managed and recorded systematically. The program also generated practical recommendations, including the separation of environmental cost records, optimization of waste utilization, and the development of simple procedures for chemical waste management. These findings demonstrate that education on quality cost identification can enhance environmental cost accounting literacy and serve as an initial step toward improving operational efficiency and supporting the sustainability of small beauty salon businesses.